A hazai mikro-, kis- és középvállalkozások külső finanszírozási lehetőségei - Bodó Imre (2015)
The chosen topic of the thesis is justified because the domestic micro, small and medium-sized enterprise (SME) sector is trying to solve the problems of funding from external sources. A wide range of external financing options are available, which was presented based on the used literature. The importance of the SME sector in both the EU and Hungary is unquestionable. The participation of companies in the national economy is crucial. SMEs contribute greatly to the economy's performance, stabilizing the function of society and economic growth, strengthen the market economy, expanding the range of goods, promote technological progress and vocational training, improving the quality of life, achievement motivated, less polluting and have significant foreign trade potential. Businesses use internal and external funding sources. The internal financing methods were not the subject of the thesis, so there is no mention of these details. The presentation of external funding opportunities includes credit, leasing, claim sales, supplier credit, customer advance payments, other loans and equity financing. The wide range of alternatives offer a variety of options, but it is necessary to consider the pros and cons of the available products. The micro, small and medium-sized enterprises face financing problems several times in the use of external resources. The firms are lack of capital, facing liquidity problems; suffer from the lack of transparency and the entrepreneurs’ low risk-taking propensity. The transaction costs of financing options are way too high for businesses and therefore they find themselves in a financing gap. The solutions for the problem are the state-supported loan programs, which provide a cheap source, with fewer obligations. The Funding for Growth Scheme, the Széchenyi loans, Venture Finance Programme and the National Microcredit Programme provide benefits for businesses. The lower costs of capital, the existence of the guarantee institutions make easier access to credit, which show up to the success of the programs. In a detailed presentation of the National Microcredit Programme drawbacks appear in addition to the benefits. The proposed changes, such as more active marketing, entrepreneurship training and the reduction of collateral requirements, would provide the development of the Programme.